ENTREPRENEURIAL ORIENTATION IN TURBULENT ENVIRONMENTS: THE EFFECT OF PRODUCTIVE ORGANIZATIONAL ENERGY TO MAKE ABSORPTIVE CAPACITY MORE EFFECTIVE. - Udut Damero; Anton Wachidin Widjaja (President University, 2021)
The COVID-19 outbreak that occurred at the end of 2019 in China and then entered Indonesia in March 2020 has given a lot of impacts on various industries, including small and medium enterprises (SMEs) that focus in food and beverage such as restaurants, cafés and others. Many studies confirmed that entrepreneurial orientation (EO) has a positive relationship with firm performance and that relationship’s dependence on several contingencies. The purpose of this study is to investigate that the positive emotional, cognitive and behavioral resources of organizational members jointly manifest as a higher-level resource (i.e. productive organizational energy) that increase the absorptive capacity (ACAP) of the organization which moderate the relationship between EO and firm performance in turbulent situation. Regarding the objectives of this model, this research will empirically validate using survey data from 50 cafés in Jakarta which selected using stratified random sampling method. Data will be analyze using partial-least-square, structural- equation model of (PLS-SEM). Our study provides useful information that could inform SMEs like cafés in Jakarta that in turbulent situation, organizational energy is needed to increases the absorptive capacity which positively moderates the relationship between EO and firm performance.Keywords: Firm performance, Entrepreneurial orientation, Absorptive capacity, Market turbulence, and Organizational energy